Konstruksi Identitas Global Dan Lokal Dalam Majalah Gogirl!: Sebuah Hibriditas (Analisis Semiotik Majalah Gogirl! Edisi 101 Bulan Juni Tahun 2013) - Mediana Utami; Muria Endah Sokowati (Program Studi Ilmu Komunikasi, 2021)
Abstract. : This research focuses on describe the position of local and global identities in hybridity. In explain the construction of local and global identities on Gogirl!, the author used semiotics of Roland Barthes. Hybridity is a resistance of local culture to global domination. Magazine assimilated the elements of global culture, devoid eliminated or defend the local elements. In this case, there are certain hybridity mechanisms that has been done, namely the use of hodgepodge language, a blend of English and bahasa Indonesia; the usage of western elements as inspiration; and maintaining the spirit of localism. The hibridity of GoGirls! is a form of negotiation to provide opportunity on the present of local identity. As an inferior subject, local identity becomes an active subject in expressing its identity at the global level through hybridity.Keywords: Hybrid Culture, Hibridity, Global Culture, Local Culture,Magazine.